Mutations at codons 178, 200-129, and 232 contributed to the inherited prion diseases in Korean patients - Choi, Bo-Yeong (BioMed Central, 2009)
BACKGROUND: Polymorphisms of the human prion protein gene (PRNP) contribute to the genetic determinants of Creutzfeldt-Jakob disease (CJD). Numerous polymorphisms in the promoter regions as well as the open reading frame of PRNP were investigated. Greater than 90% of Korean, Chinese, and Japanese carry the homozygote 129 MM codon. In Korea, polymorphisms have not been comprehensively studied, except codons 129 and 219 in PRNP among Korean CJD cases. Although polymorphisms at codons 129 and 219 play an important role in susceptibility to sporadic CJD, patients with other polymorphisms in PRNP exhibited critical distinctions of clinical symptoms. METHODS: The genetic analyses of PRNP were carried out among probable CJD patients in comparison with the results from magnetic resonance imaging (MRI) and electroencephalogram (EEG). RESULTS: The molecular analyses revealed that three mutations at codons D178N, E200K, and M232R in heterozygosity. Patients with the D178N and M232R mutations had a 129MM codon, whereas the patient with the E200K mutation showed 129MV heterozygosity. They all revealed strong 14-3-3 positive signals. The 67-year-old patient with the D178N-129M mutation showed progressive gait disturbance and dysarthria was in progress. The 58-year-old patient with the E200K mutation coupled to the 129MV codon had gait disturbance, dysarthria, agitation, and ataxic gait, and progressed rapidly to death 3 months from the first onset of symptoms. The 65-year-old patient with the M232R mutation showed rapidly progressive memory decline and gait disturbance, and died within 16 months after onset of symptoms. CONCLUSION: Despite differences in ethnicity, the clinical and pathological outcomes were similar to the respective mutations around the world, except absence of insomnia in D178N-129M subject.